Penerapan Model Pembelajaran Problem Based Learning Berbasis Kuis Interaktif Untuk Meningkatkan Hasil Belajar Pada Mata Pelajaran Matematika Kelas Iv SD Negeri Jatiurip 1 - Inayatul karimah; Ribut Prastiwi Sriwijayanti; Ludfi Arya Wardana (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2025)
This study originated from the problem of many fourth grade students at SDN Jatiurip 1 who get low learning scores. In addition, in the teaching and learning process, the materials used are only LKS, without any variation of other teaching materials. Due to these various problems, the researcher planned to conduct research using the class action research method, to observe and improve the problems faced by fourth grade students. The purpose of this study was to improve student learning outcomes in grade IV math at SDN Jatiurip 1 after the application of the PBL learning model using interactive quizzes. This type of research is a class action research (PTK) with a focus on class IV students consisting of 15 people. The model used in this research refers to Kemmis and Mc Taggart. The research was conducted in 2 cycles, and each cycle involved 2 meetings. Each cycle consists of 4 stages, namely planning, implementing actions, observing, and reflecting. Based on the research conducted, in the first cycle, the level of student learning engagement reached 64.2%, while in the second cycle it increased to 83.93%. This increase was due to the use of interactive quiz after learning with PBL model. In addition, in cycle I, the average percentage of students who achieved learning standards was 46.6% of a total of 15 students, while in cycle II, the average learning outcomes increased to 86.6%. Student learning data was obtained from analyzing the pretest and posttest scores done by the students. From the results of this study, it can be concluded that the interactive quiz-based PBL model proved effective in improving student learning outcomes in mathematics subjects about fractions worth.